Haemophilus parasuis infection in 3D4/21 cells induces autophagy through the AMPK pathway. (26th April 2019) - Shen, Yijuan; Zhou, Nini; An, Jiahui; Zhang, Jiansong; Wang, Meifen; Li, Yufeng; Jiang, Ping
Abstract: Haemophilus parasuis ( H. parasuis ) is a common commensal in the upper respiratory tract of pigs, but causes Glässer's disease in stress conditions. To date, many studies focused on the immune evasion and virulence of H. parasuis ; very few have focused on the role autophagy played in H. parasuis infection, particularly in porcine alveolar macrophages (PAMs). In this study, a PAM cell line, 3D4/21 cells were used to study the role of autophagy in H. parasuis infection. 3D4/21 cells tandemly expressing GFP, mCherry, and LC3 were infected with H. parasuis serovar 5 ( Hps 5). Western blot analysis and confocal and transmission electron microscopy showed that H. parasuis infection effectively induces autophagy. Using Hps strains of varying virulence ( Hps 4, Hps 5, and Hps 7) and UV‐inactivated Hps 5, we demonstrated that autophagy is associated with the internalisation of living virulent strains into cells. In 3D4/21 cells pretreated with rapamycin and 3‐MA then infected by Hps4, Hps5, and Hps7, we demonstrated that autophagy affects invasion of H .  parasuis in cells. AMPK signal results showed that Hps5 infection can upregulate the phosphorylation level of AMPK, which is consistent with the autophagy development. 3D4/21 cells pretreated with AICAR or Compound C then infected by Hps 5 revealed that the autophagy induced by Hps 5 infection is associated with the AMPK pathway. Our study contributes to the theoretical basis for the study of H. parasuis pathogenesis and development of novel drugs target for prevention Glässer's disease.